THE ROLE OF ZAKAH AND BINARY ECONOMICS IN POVERTY REDUCTION - Muniaty Aisyah (Esensi: Jurnal Bisnis dan Manajemen, 2014)
Poverty reduction remains the most important challenge for every countries. Zakah, as an Islamic faith-based institution, is a strategic tool for combating poverty.  This study aims to identify the role of zakah and compare its principles with an overview of the characteristics and practices within binary economics which also provides a systemic solution for poverty. The study shows that zakah has an essential role to  the economic growth and poverty reduction in Muslim community, as well as, binary economics which also offers a way of enhanching everyone’s economic well-being and fundamentally different from all forms of conventional economics.DOI: 10.15408/ess.v4i1.1964